Roles of Husbands and Wives in the Christian Marriage Relationship (Ephesians 5) - Nina Lovše (Kairos (English Ed.))
Partners within the marriage relationship are equal before God because both were made in his image. Together they fully reflect the image of God. They are both bearers of the personality of God; both present the distinctive aspects of the character of God. However, husbands and wives received different roles. Within the context of the Christian marriage, as presented in Ephesians 5, partners are called to lovingly submit to one another. In light of that mutual submission, wives are specifically exhorted to submit to their husbands and husbands are specifically exhorted to love their wives. Husbands and wives are compared to Christ and the church, thus giving this relationship a special purpose and meaning, a unique place in the range of biblical relations, presenting it as meaningful, authoritative and vital. There certainly are some limitations to the cultural aspect of the roles, however, the comparing of this relationship to Christ and the church gives the roles within the marriage an eternal, culturally transmittable value. Christ will always remain the head of his church and will always love his bride, and the church will be forever called to submit to him and respect him.